1966
DOI: 10.1104/pp.41.8.1381
|View full text |Cite
|
Sign up to set email alerts
|

Organs of Gibberellin Synthesis in Light-Grown Sunflower Plants

Abstract: Summnary. The sites of gibberellin (GA) synthesis in light grown sunflower plants were studied. The results of organ excision and the exogenous application of indole acetic acid and gibberellic acid indicated that gibberellin synthesis occurred in the young leaves of the apical bud. This was substantiated using a combination of diffusion and extraction techniquies. Diffusion of suinflower apical buds on agar for 20 hours revealed a level of gibberellin greater than that obtained by solvent extraction of a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

1969
1969
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(60 citation statements)
references
References 11 publications
3
57
0
Order By: Relevance
“…The experiments described here indicate that the root-synthesized GA has no direct controlling effect on pea stem growth (Table I). The mechanism controlling pea stem growth must be located in the stems, presumably near the apex, and the stem-synthesized GA (6,12,16) is presumed to be a factor in this mechanism (7,11). Based on our grafting experiments, the stem-synthesized GA must be the dominant controlling factor because dwarf pea stems grew the same amount whether they were grafted onto tall or dwarf rootstocks (Table I).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The experiments described here indicate that the root-synthesized GA has no direct controlling effect on pea stem growth (Table I). The mechanism controlling pea stem growth must be located in the stems, presumably near the apex, and the stem-synthesized GA (6,12,16) is presumed to be a factor in this mechanism (7,11). Based on our grafting experiments, the stem-synthesized GA must be the dominant controlling factor because dwarf pea stems grew the same amount whether they were grafted onto tall or dwarf rootstocks (Table I).…”
Section: Discussionmentioning
confidence: 87%
“…Since Went (17,18) (6,12,16). Lockhart (10) attempted to demonstrate the controlling aspect of shoot tip-syhthesized gibberellin by grafting a stem from a tall pea onto the root of a dwarf pea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several workers have shown that root exudates contain kinetin-like activity (8,13,14) as well as gibberellin activity (25,28). The root tips are production sites for both cytokinins (30) and gibberellins (9,10). Rootless plants have not been extensively used to study the effect of hormones produced by the roots on shoot growth.…”
mentioning
confidence: 99%